Effects of reclaimed water discharge in the Maneadero coastal aquifer, Baja California, Mexico. (May 2018) - Gilabert-Alarcón, Christian; Daesslé, Luis W.; Salgado-Méndez, Saúl O.; Pérez-Flores, Marco A.; Knöller, Kay; Kretzschmar, Thomas G.; Stumpp, Christine
Abstract: Since 2014, reclaimed water has been used for agricultural irrigation and it has been discharged on a riverbed of the Maneadero aquifer, Baja California, Mexico. To determine the effects of reclaimed water on groundwater quality, samples of reclaimed water and groundwater were collected spatiotemporal and analyzed using stable isotope (δ 18 OH2O, δ 2 HH2O, δ 18 ONO3 and δ 15 NNO3 ) and geochemical signatures, jointly with multivariate statistical methods and a 2D resistivity tomography. Reverse ion exchange and mineralization are the main processes influencing the groundwater composition. The Cl/Br ratios identified seawater intrusion and solid waste, wastewater and animal waste as the main sources responsible for these processes, overlapping with the ratios of reclaimed water. Nitrates are pervasive throughout the aquifer and δ 18 ONO3 and δ 15 NNO3 attributed wastewater and animal waste as the major nitrates inputs. Multivariate statistics were able to separate seawater and human-derived processes. The δ 18 OH2O and δ 2 HH2O showed the effect of mixing with d -excess of 5–6‰, indicating recharge other than precipitation. A mixing model using Cl − and δ 18 OH2O and principal components revealed the mixing proportion of seawater; whilst the over- and under-estimates of reclaimed water contribution are indicative of missing end-members. The Na-Cl-Br-B systematics, however, suggest that reclaimed water result in cation-exchange and adsorption reactions and once the adsorbed sites become saturated with respect of Na +, Br − and B − can be reflected in the groundwater composition. Additionally, resistivities indicate that reclaimed water interacts between the fresh and brackish groundwater. Monitoring the efficiency of the vadose zone to retain contaminants and distinguish them from reclaimed water is essential for evaluating groundwater quality. Graphical abstract: Image 1 Highlights: Influence of reclaimed water on coastal groundwater quality is investigated. Isotopic and geochemistry data was applied to identify the mix of reclaimed water. Reclaimed water was comparable to that of groundwater mixed with urban wastewater. Reclaimed water resulted in cation-exchange and adsorption reactions.